2014
DOI: 10.3746/jkfn.2014.43.3.446
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Activity and Quality Characteristics of Rice Madeleine Added with Pine Needle Powder and Extract

Abstract: To develop health functional gluten-free rice madeleines added with pine needle, rice flours were prepared by adding different contents (0.6, 1.2, and 1.8% on rice flour basis) of freeze-dried pine needle powder (PP) and extract (PE, by pressing pine needles). The preparation, textural and sensory properties, and antioxidative activities of rice madeleines were investigated. The antioxidative activities of rice madeleines added with PP and PE were higher than those of the control and were significantly differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Korean red pine (Pinus densiflora) belongs to the Pinaceae family and is widely distributed in Korea and in the other areas of East Asia (Kim, 1996). Needles, cones, bark, and pollen of Korean red pine have been used for medicine and safe food raw materials (Kim et al, 2012). Although many studies on the chemical components and biological activities have been reported on the extracts of Korean red pine leaves and branches, but the researches on the bark extracts have still plenty of room to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Korean red pine (Pinus densiflora) belongs to the Pinaceae family and is widely distributed in Korea and in the other areas of East Asia (Kim, 1996). Needles, cones, bark, and pollen of Korean red pine have been used for medicine and safe food raw materials (Kim et al, 2012). Although many studies on the chemical components and biological activities have been reported on the extracts of Korean red pine leaves and branches, but the researches on the bark extracts have still plenty of room to be conducted.…”
Section: Introductionmentioning
confidence: 99%